Gas sector reforms in India: How will it change the market outlook? - Nitin Zamre (The Oxford Institute for Energy Studies, 2023)
The Indian gas sector is expected to be one of the world's fastest-growing markets over the next two decades. Yet there is a wide divergence of views around India's future gas demand and the potential for gas to reach this share. The affordability of gas remains central to this ambition. The future of India's domestic industrial structure and pricing policies are key factors in determining the outlook for gas in the country's energy mix. This paper first looks at the background of gas prices in India and the evolution of market-based mechanisms, before going on to consider how these have impacted upstream production and the implications for demand.
Keywords: 330; Demand; Gas; India; LNG; price reform; Upstream